EP.WE.484Conservative management of post-operative chyle leak after surgery for a large adrenal cavernous haemangioma. (28th October 2021) - Quake, Sharmaine Yen Ling; Chua, Yunli; Elsaify, Wael
Abstract: Post-operative chyle leak is a rare but recognised complication after abdominal surgeries particularly those involving dissection adjacent to the retroperitoneal lymph nodes and/or lymphatic systems. There are limited cases of post-operative chyle leak associated with adrenal surgery reported in the literature with no consensus on its management. Lymphatics of the adrenal gland drain into the thoracic duct via regional lymph nodes or directly into the cisterna chyli, posterior to the aorta. If not adequately managed, chyle leak can be associated with hypovolemia, electrolyte imbalances, malnutrition and immunosuppression. These consequences can be attributed to the loss of fluid, electrolytes, lipids, proteins, and immunoglobulins. We hereby report a case of post-operative chyle leak in a 79-year-old male who underwent an open left adrenalectomy, left nephrectomy, splenectomy and distal pancreatectomy for a large, 20.8cm left adrenal cavernous haemangioma. Chyle leak was confirmed on post-operative day 7 based on high levels of triglycerides in the abdominal drain output. Intra-operatively there was no evidence of lymphatic damage. However, the major abdominal surgery involving retroperitoneal viscera close to the lymphatic trunk predisposed the patient to this complication. The patient was managed conservatively with the aim of decreasing chyle production by dietary manipulation and use of somatostatin. Enteral nutrition was continued with a strict low-fat diet and regular dietician input. These strategies contributed to the gradual resolution of chyle leak and the patient's recovery.